ANALYSIS OF THE USE OF THE TYPING MASTER APPLICATION IN STUDENTS OF OFFICE ADMINISTRATION EDUCATION AT THE STATE UNIVERSITY OF SURABAYA USING TAM - Inka Agustin Rokhmawati; Jaka Nugraha (Jurnal TAM (Technology Acceptance Model), 2021)
This research is focused on users typing master in students in the Office Administration Education Study Program at State University of Surabaya to analyze how the influence of subjective norms, perceived ease of use and perceived usefulness on intentions to use behavior. This study uses quantitative research method with primary data analysis techniques using a questionnaire that is taken to the respondents. Data analysis method using Partial Least Square (PLS) managed using SmartPLs 3.0 software. The results shows that subjective norms have a positive and significant effect on usage behavior intention, perceived ease of use have a positive and insignificant effect on usage behavior intentions, perceived usefulness have a positive and significant effect on usage behavior intentions and perceived ease of use have a positive and significant effect on usage behavior intentions through perceived usefulness.